2019
DOI: 10.1088/1748-9326/aaf3d3
|View full text |Cite
|
Sign up to set email alerts
|

Advancing global flood hazard simulations by improving comparability, benchmarking, and integration of global flood models

Abstract: In recent years, a range of global flood models (GFMs) were developed, each utilizing different process descriptions as well as validation data sets and methods. To quantify the magnitude of these differences, studies assessed the performance of GFMs only on the continental and catchment level. Since the default model set-ups resulted in locally marked deviations, there is a clear need for further and especially more standardized research to not only maintain credibility, but also support the application of GF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…However, global flood risk assessment obtained by machine learning methods is only a static result rather than a dynamic one, and the physically based model has an advantage. A physically based model can often give more detailed information on flood hazards, such as flow and submerged range, while current machine learning studies focus on qualitative assessment of flood hazards [21][22][23]. These qualitative evaluations can only provide limited reference for watershed management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, global flood risk assessment obtained by machine learning methods is only a static result rather than a dynamic one, and the physically based model has an advantage. A physically based model can often give more detailed information on flood hazards, such as flow and submerged range, while current machine learning studies focus on qualitative assessment of flood hazards [21][22][23]. These qualitative evaluations can only provide limited reference for watershed management.…”
Section: Discussionmentioning
confidence: 99%
“…These methods are based on expert knowledge and are susceptible to uncertainty [19]. Physically based models such as VIC and MIKE models at a regional scale, and other hydrological models at the continental and global scale have also been used to study floods, and have shown great advantages in regional or global flood process research [8,[20][21][22][23]. Recently, machine learning methods such as artificial neural networks (ANN), support vector machines (SVM), and decision trees (DT) have been applied to flood hazard assessments, which can identify and evaluate flood-prone areas based on the training and testing of large amounts of data [24][25][26][27].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous studies, 80 no relationship was found between performance and model spatial resolution. In a follow-up study, Hoch and Trigg (2019) proposed a global flood model validation framework. The aim of this framework is to understand the drivers of deviations between GFMs by providing standard forcing data, validating and benchmarking model results, and by sorting and indexing reference output.…”
Section: Introductionmentioning
confidence: 99%
“…In order to get a better understanding of which of these characteristics has the largest influence on overall model performance, a 510 systematic comparison framework is required, in which each of these modeling components and parameters can be tested individually and in unison. The proposed model comparison framework of Hoch and Trigg (2019) could therefore greatly benefit our current understanding of global flood hazard.…”
mentioning
confidence: 99%